Influence of Simulation Games Technique on Content Mastery Service to Understanding Student Learning Styles - Puspita, Puput; Rakhmawati, Dini (International Journal of Active Learning, 2018)
This study aims to determine the effect of simulation games techniques through content mastery services to the understanding of student learning styles. The type of this research is quantitative research with quasi exsperimental design design using nonequivalent control group design. Samples taken were 62 students of class XI IPS 1 and IPA 5 by using cluster random sampling technique. Based on the results of calculations using t test obtained t count> ttable at 5% significance level with db 60 that is 2.537> 1.671. It can be concluded that simulation games technique through content mastery service can improve understanding of student learning style of class XI SMA Negeri 1 Gubug.